Two wheeled balanced vehicle - Mohd Haziq, Khairul Salleh (2013)
This project discusses about the development of a 2 wheel balanced autonomous robot based on the inverted pendulum model. The vehicle is designed to achieve stability as it stand still and able to move around a smooth terrain without falling. An IMU which consist of triple-axis accelerometer and dual-axis gyroscope was chosen as the sensor to calculate the tilt angle of the robot. This sensor needed to be placed near the centre of the robot to make the reading more accurate. A processing unit chosen is the Arduino Mega, a PlC based microcontroller which can be used to read both the data send from the sensor and the motor encoder. It can also send the output signal towards the motor and can easily be program by the use of its own programming language. A PID controller is used in order to calculate the "error" value as it finds the difference between the desired output and the measured outcome. This value is then sent as a feedback data towards the input to adjust and minimize the error.